A rapid review of the effect of assistive technology on the educational performance of students with impaired hearing. (2nd October 2020) - Bell, Diane; Foiret, Jaudon
Abstract: Purpose: To review the knowledge base regarding assistive technology (AT) and the education of people with a hearing impairment. Also, evaluating to what extent has the use and/or impact of AT for individuals with a hearing impairment been determined through evidence-based research in post-school education. Materials and method: Literature pertaining to the effect of AT on the educational performance of students with impaired hearing in the post-school sector was examined for the period from 1998 to 2018 (20 years). A total of 477 articles that contained evidence-based research and reports on the effect of AT in practice were located and reviewed. Results: It was found that, of the 20 studies that met all the inclusion criteria, only seven provided promising, evidence-based reports on the impact of assistive hearing technology on educational performance. Conclusion: This review concluded that the limited research speaks to the positive impact of AT on educational outcomes. Additionally, for students with a hearing impairment to be able to receive high-quality AT that will enhance their educational success, more evidence-based research on the efficacy of hearing AT needs to be conducted, especially as newer technologies emerge in this technological era. Implications for rehabilitation: The use of appropriate hearing assistive technology (AT) is a key facilitator within the educational environment and has a positive impact on the educational outcomes for students studying at college or university. This rapid review revealed the need to develop a body of scientifically based research that examines the relationship between academic achievement of participation by deaf learners and the use of AT – this is needed to develop a more comprehensive understanding of the benefits and limitations of educational technologies, especially as newer technologies emerge in this technological era. This study further highlights the need for more concrete research on the effectiveness of hearing-related AT so that the case can be made for students with hearing impairment to receive high quality, appropriate AT that will enhance their educational success. Ultimately, it is hoped that this article elicits the need for much more investigation into this topic to work towards finding solutions that lead to increased participation of deaf learners in the higher education arena, as well as providing evidence-based results to inform future policy and practice.